A mathematical model for condensation of bubbles injected through an orifice into subcooled water - (:unkn) unknown (SILA SCIENCE, 2010)
In this investigation, a semi-empirical equation is developed to predict the collapse rate of steam bubbles injected through an orifice into subcooled water. The equation considers both bubble distortion and the heating of the liquid around the condensing bubble. The theoretical predictions correlate experimental data reasonably well.
Keywords: Cooling; Condensation; Mathematical modeling; HEAT-TRANSFER; LIQUID; PHASE